(untitled) (Vegueta: Anuario de la Facultad de Geografía e Historia, 2016)
En el Archipiélago Canario y sobre todo en los cabildos de las dos principales islas, Tenerife y Gran Canaria, son escasas las referencias a las conmemoraciones por el fallecimiento de los monarcas. Las actas capitulares recogen, de forma lacónica, las obligaciones de «tristura» con descripciones muy parcas. No obstante, aunque con medios muy escasos, las celebraciones de los funerales regios se realizaron siguiendo lo estipulado en la legislación, independientemente de la distancia espacial y social de estos nuevos territorios. In the Canary Islands, and above all in the Cabildos (Island Executive Assemblies) of the two principal islands, Tenerife and Gran Canaria, there are few references to the ceremonies of commemoration for the deaths of the Catholic King and Queen (Ferdinand and Isabella). The minutes of Cabildo meetings include, very succinctly, the obligations of formal mourning, with only the briefest of descriptions. Nevertheless, even though resources were very scarce, the services commemorating the passing of the King and Queen were carried out following the legally stipulated rules, in spite of the physical and social distances of these new territories.